Association between plasminogen activator inhibitor‐1 and severity of liver injury and cardiovascular risk in children with non‐alcoholic fatty liver disease. Issue 1 (20th October 2016) - Jin, R.; Krasinskas, A.; Le, N‐A.; Konomi, J. V.; Holzberg, J.; Romero, R.; Vos, M. B.
Summary: Background: Plasminogen activator inhibitor‐1 (PAI‐1) is the primary inhibitor of the endogenous fibrinolytic system and is known to be increased in obesity, insulin resistance and non‐alcoholic fatty liver disease (NAFLD). We previously demonstrated that PAI‐1 levels were closely related to the amount of hepatic steatosis in children. Objectives: The aim of this study was to characterize plasma PAI‐1 in relationship to severity of inflammation and fibrosis, as well as to plasma lipids in children with NAFLD. Methods: In 44 children with NAFLD, plasma PAI‐1 levels and lipids were measured at the time of a liver biopsy. Hepatic histological features were systematically scored. Trend analysis was applied to determine the correlation of plasma PAI‐1 levels with lipid markers for cardiovascular disease and with the staging of histological features in the liver. Results: We found that plasma PAI‐1 levels were significantly increased in children with increased severity of steatosis, lobular inflammation, ballooning and fibrosis. Furthermore, PAI‐1 was strongly correlated with plasma lipids and insulin resistance indices. Conclusions: PAI‐1 appears to be tightly related to both histologic severity of NAFLD as well as systemic features of the disease including insulin resistance and dyslipidemia. PAI‐1 may be a mediator of disease progression and future cardiovascular complications in children with NAFLD.